PENGARUH LINGKUNGAN KERJA NON FISIK DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA PEGAWAI PADA STISIP AMAL ILMIAH YAPIS WAMENA - - Tukijan (Master of Public Administration, Universitas Slamet Riyadi, 2016)
Effect Of Non Physical Work Environment And Physical WorkEnvironment On The Job Satisfaction Of Employees Charity ScientificStisip.The porpose in this research to analizyng influence of Enviroment of workconcerning official satisfaction of work in college of Social Science andpolitical Science of Amal ilmiah of Foundation of Muslim Education ofWamena.kind of research is assosiative with Quantitative methad .Data ofresearch gets by Questioner and 0bservation.TO take sample use totalingsampling is 28 people.in technic of data analized use regression byscalelcker. Result of research show that, to analized 3 hypothsis by SPSS16.0 that ; 1 )Variabele of NON Physical Enviratment of work in partialinfluence concerning official satisvaction of work in College of SocialScience and political Science of Amal ilmiah of Foundation of MuslimEducation of Wamena.2) variabele of physical Environment of work inpartial is’nt influence concerning official satisfaction of work in college ofSocial Science and political Science of Amal ilmiah of Foundation ofMuslim Education of Wamena.3) Variabele of NON PhysicalEnvironment of work and Physical Environment of work in simultanceuosinfluence concerning official satiafaction of work in College of SocialScience and Political Science of Amal ilmiah of Foundation of MuslimEducation of Wamena.Key words : Enviroment of work, Employees, Satisfaction.